Strategy with duty drawback to help developing boost exports in central javanese - Fika Ahmad; Qristin Violinda; Ika Indriasari (KINERJA, 2020)
This study aims to analyze the use of duty drawback by using IKM KITE facilities in the Central Java region. Qualitative research methods are used to explore in depth the questions in this study using the Atlas.ti analysis tool. Researchers conducted semi-structured interviews with providers and target duty drawback users of the KITE IKM facility. Based on the results of the interviews showed that the factors that hindered the use of KITE IKM KITE facility duty drawback were the high dependence of the IKM on distributors, the inability to meet the export period, the lack of confidence in the IKM, and the absence of synergy between related agencies. Several solutions are offered to improve the smooth use of the IKM KITE facility. This research contributes both practical and theoretical.